Perancangan Infografis Zoonosis (Penyakit yang ditularkan Anjing dan Kucing) - Febri Ramadoni Putra; hendra afriwan; dini faisal (Universitas Negeri Padang, 2020)
Zoonosis infographic design (a disease transmitted by dogs and cats) using poster media. The purpose of this infographic design is to educate or increase knowledge and to remind the public of dogs and cats that can transmit Zoonosis. This infographic describes a carrier or animal carrier of disease, mode of transmission, symptoms, treatment and prevention.The design method used is the glass box method and includes the collection of data through Non-Participant observation at the Padang City Health Office to obtain valid data about the disease. Secondary data were obtained from manuals and supporting articles available on the internet. The analytical method used in analyzing data that has been collected is believed to use the 5W + 1H data analysis method. The main media for infographics are posters, and using supporting media: stickers, pins, key chains, tissue boxes, mugs, pencil cases, calendars, flyers and glossary bookmarks.Keywords: Infographics, Zoonosis, posters, rabies